2012
DOI: 10.1258/jhsrp.2011.010109
|View full text |Cite
|
Sign up to set email alerts
|

Climate for Evidence-Informed Health Systems: A Profile of Systematic Review Production in 41 Low- and Middle-Income Countries, 1996-2008

Abstract: In many countries, those seeking to support evidence-informed health systems cannot turn to experienced local systematic reviewers to help them to find and use systematic reviews or to conduct reviews on high priority topics when none exists. These findings suggest the need for local capacity-building initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…The number of Cochrane review authors is growing in Africa and Nigeria produces most of the systematic reviews, followed by Kenya and Uganda (Mbuagbaw, 2013;Law et al, 2012). In this study, we found no Cochrane review authors, contributors to Cochrane or research output from Namibia.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The number of Cochrane review authors is growing in Africa and Nigeria produces most of the systematic reviews, followed by Kenya and Uganda (Mbuagbaw, 2013;Law et al, 2012). In this study, we found no Cochrane review authors, contributors to Cochrane or research output from Namibia.…”
Section: Discussionmentioning
confidence: 51%
“…We searched the Archie database to assess Namibian contributors. To verify Namibia's research capacity and outputs, we searched and assessed the Cochrane colloquium abstracts site (2015) and the systematic review by Law et al, (2012). Table 1 shows the survey structure and synopsis of the outcome measures.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…This may be linked to the fact that the production of Health Policy and Systems Research (HPSR) is still in its infancy in these countries [5456]. …”
Section: Discussionmentioning
confidence: 99%
“…Systematic review output by EMR member state researchers has improved since the mid-1990s, but it continues to lag behind middle-and lowincome country comparators. 22 Clinical trial registration by member states, meanwhile, has increased strikingly from a very low base in 2004, but this is overwhelmingly due to research activity in one country -Iran. 23 Creating and sustaining resources for health research…”
Section: Producing and Using Health Researchmentioning
confidence: 99%